Development of cell‐based high throughput luminescence assay for drug discovery in inhibiting OCT4/DNA‐PKcs and OCT4–MK2 interactions. Issue 5 (1st March 2021) - Mohiuddin, Ismail S.; Wei, Sung‐Jen; Yang, In‐Hyoung; Martinez, Gloria M.; Yang, Shengping; Cho, Eun J.; Dalby, Kevin N.; Kang, Min H.
Abstract: Amplification‐independent c‐MYC overexpression is suggested in multiple cancers. Targeting c‐MYC activity has therapeutic potential, but efforts thus far have been mostly unsuccessful. To find a druggable target to modulate c‐MYC activity in cancer, we identified two kinases, MAPKAPK2 (MK2) and the DNA‐dependent protein kinase catalytic subunit (DNA‐PKcs), which phosphorylate the Ser111 and the Ser93 residues of OCT4, respectively, to transcriptionally activate c‐MYC. Using these observations, we present here a novel cell‐based luminescence assay to identify compounds that inhibit the interaction between these kinases and OCT4. After screening approximately 80, 000 compounds, we identified 56 compounds ("hits") that inhibited the luminescence reaction between DNA‐PKcs and OCT4, and 65 hits inhibiting the MK2–OCT4 interaction. Using custom antibodies specific for pOCT4 S93 and pOCT4 S111, the "hits" were validated for their effect on OCT4 phosphorylation and activation. Using a two‐step method for validation, we identified two candidate compounds from the DNA‐PKcs assay and three from the MK2 assay. All five compounds demonstrate a significant ability to kill cancer cells in the nanomolar range. In conclusion, we developed a cell‐based luminescence assay to identify novel inhibitors targeting c‐MYC transcriptional activation, and have found five compounds that may function as lead compounds for further development. Abstract : A schematic overview of the initial screening and two‐step hit validation is presented. Initial screening of a chemical library identified 65 hits. These compounds were validated for their reduction effect of phospho‐OCT4 and MYC as well as the binding inhibition of OCT4 and MK2/DNA‐PKcs. Two aspects of the method are novel: 1. A mammalian cell system exogenously expressing equimolar proteins. 2. Expression of the fragment of DNA‐PKcs interacting with OCT4 to overcome the size issue (450 kDa) for the assay. α .